A fatal attack caused by a lowland tapir (Tapirus terrestris) in Southeastern Brazil - Haddad Júnior, Vidal [UNESP]; Assunção, Melissa Chagas [UNESP]; De Mello, Ricardo Coelho [UNESP]; Duarte, Marcelo Ribeiro [UNESP] (SAGE Publications, 2005)
A 55-year-old man was attacked by a Brazilian tapir (Tapirus terrestris) after surprising and stabbing the animal in his corn plantation. The victim received deep bites in the thighs, neck, and cervical areas, resulting in severe hemorrhage and death. This is the first report of a tapir incident resulting in death and is of interest because of the severity of the contusions and lacerations caused by the provoked animal.
Keywords: Animal attack; Bites; Tapir; Tapirus terrestris; Teeth marks; adult; animal behavior; bite; bleeding; Brazil; case report; cervical spine; death; human; male; neck; nonhuman; thigh; Animals; Animals, Wild; Bites and Stings; Diagnosis, Differential; Fatal Outcome; Female; Humans; Male; Middle Aged; Perissodactyla